(untitled) (Third Sector Social Economic Review, 2023)
In today’s competitive environment, where knowledge management is seen as valuable and strategic assets, it is thought that organizational performance will increase with its inclusion in business processes. The purpose of this study is to investigate the relationship between knowledge management, organizational agility and organizational performance. In this direction, the moderating effect of organizational agility on the relationship between knowledge management tendency and organizational performance was investigated. In addition, the effect of demographic characteristics of employees on organizational performance is examined. The proposed model was analyzed with the data obtained through a survey conducted on employees in a metal production enterprise. The findings confirm the positive effects of knowledge management on organizational performance and organizational agility. It is seen that there is a positive low level significant relationship between the perception dimension of organizational agility and the knowledge sensitivity dimension of knowledge management, and a positive low level significant relationship between the financial performance sub-dimension of organizational performance and the organizational memory dimension of knowledge management. It has been determined that knowledge management has the most significant effect on the taking action dimension among the sub-dimensions of organizational agility. It has been determined that organizational agility affects operational performance more than financial performance. It is concluded that knowledge management affects financial performance more than operational performance. In addition, it has been seen that knowledge management has a regulatory role in the effect of knowledge management on organizational performance because it increases the effect of organizational agility.